2012
DOI: 10.1002/app.36633
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization and multiple melting behaviors of β‐nucleated impact‐resistant polypropylene copolymer

Abstract: As a substitute of isotactic polypropylene in applications requiring excellent fracture resistance, impact-resistant polypropylene copolymer (IPC) has attracted much attention in recent years. In this study, a highly effective b-form nucleating agent (b-NA; an aryl amide compound) was introduced into IPC, and our attention was focused on the nonisothermal crystallization and subsequent melting behaviors of the nucleated samples. The nonisothermal crystallization behaviors were investigated on the basis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…It is observed that the relative fraction of β‐crystal indeed decreases with increasing in cooling rate. This result is different from that reported by Wang and coworkers . They observed that the relative fraction of β‐crystal slightly increases with the cooling rate when the cooling rate is smaller than 20°C/min.…”
Section: Resultscontrasting
confidence: 99%
“…It is observed that the relative fraction of β‐crystal indeed decreases with increasing in cooling rate. This result is different from that reported by Wang and coworkers . They observed that the relative fraction of β‐crystal slightly increases with the cooling rate when the cooling rate is smaller than 20°C/min.…”
Section: Resultscontrasting
confidence: 99%
“…However, due to the thermodynamic instability of the β‐modification, it can be rarely obtained in a significant amount in commercial iPP products, unless the crystallization conditions are favorable for the β‐modification growth. There are some approaches to obtain high proportion of β‐modification, for example, crystallization under a high degree of supercooling, quenching the melt to a certain temperature gradient, shearing or elongation of the melt during the crystallization or adding the β‐nucleating agent (β‐NA) . Among these, the addition of β‐NA is a reliable, simple operating, high repeatability and currently the only one industrialized way to obtain high content of β‐modification …”
Section: Introductionmentioning
confidence: 99%
“…Some important factors are normally considered to influence the property of IPC, like the inherent structures (molecular weight, molecular weight distribution, compatibility between rubbery EPR phase and hPP matrix, and the morphology of dispersed phase) and the external parameters (temperature , and fillers , ). To further expand the application of IPC, a large amount of research have been conducted to improve its toughness, mainly by means of optimizing crystalline polymorphism by adding a β-nucleating agent. Luo et al investigated the effect of phase morphology on the toughening behavior of IPC with a β-nucleating agent. The β-nucleated IPC showed a highly improved toughness under 0 °C as the content of the β-nucleating agent increased.…”
Section: Introductionmentioning
confidence: 99%